Turbidity Currents With Equilibrium Basal Driving Layers: A Mechanism for Long Runout - R. Luchi; S. Balachandar; G. Seminara; G. Parker (Geophysical Research Letters)
Abstract Turbidity currents run out over 100 km in lakes and reservoirs, and over 1,000 km in the ocean. They do so without dissipating themselves via excess entrainment of ambient water. Existing layer‐averaged formulations cannot capture this. We use a numerical model to describe the temporal evolution of a turbidity current toward steady state under condition of zero net sediment flux at the bed. The flow self‐partitions itself into two layers. The lower “driving layer” approaches an invariant flow thickness, velocity profile, and suspended sediment concentration profile that sequesters nearly all of the suspended sediment. This layer can continue indefinitely at steady state over a constant bed slope. The upper “driven layer” contains a small fraction of the suspended sediment. The devolution of the flow into these two layers likely allows the driving layer to run out long distances.